Utilization of Water Hyacinth Leaves for Protein Protection in Goat Diets: Impacts on Production Performance and Meat Quality - Sondakh, Erwin Hubert Barton; Kalele, Jerry; Hadju, Rahmawaty (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
This study aimed to evaluate the effect of using water hyacinth (Eichhornia crassipes) leaves as a natural feed protein protector on production performance and meat quality in goats. A total of 16 male goats (±15 kg body weight) were used in a completely randomized design with four dietary treatments: R1 (15% tofu dregs + 15% concentrate + 70% forage), R2 (15% tofu dregs + 1% water hyacinth leaves + 14% concentrate + 70% forage), R3 (15% tofu dregs + 2% water hyacinth leaves + 13% concentrate + 70% forage), and R4 (15% tofu dregs + 3% water hyacinth leaves + 12% concentrate + 70% forage). The goats were reared for 10 weeks to measure feed intake and average daily gain (ADG), followed by slaughter to evaluate carcass characteristics and meat chemical composition. Data were analyzed using analysis of variance (ANOVA), and treatment differences were assessed using Duncan's multiple range test. Results showed that inclusion of water hyacinth leaves significantly increased feed intake, ADG, hot and cold carcass weight, carcass percentage, and meat protein content (P<0.05). Supplementing goat diets with 1–3% (dry matter basis) water hyacinth (Eichhornia crassipes) leaves as a natural protein protection strategy significantly improves feed intake, average daily gain, carcass traits, and meat protein content. These findings demonstrate the potential of water hyacinth leaves as a functional feed additive to enhance the productivity and meat quality of goats.